2008
DOI: 10.1177/070674370805300109
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Mental Health Care for the Homeless: The Role of Psychiatry in Positive Housing and Mental Health Outcomes

Abstract: Care by a mental health specialist is positively associated with improved outcomes. Strategies to improve treatment adherence, access to mental health specialists, and innovative approaches to treatment of substance use disorders should be considered for this population. Having a psychiatrist as a member of a shelter-based collaborative care team is one possible way of addressing the complex physical and mental health needs of homeless individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…With regards to housing, significant reductions in the mean number of days spent in shelters and streets were observed in both groups over the follow-up period. This finding is consistent with an earlier study by Stergiopoulos et al[ 40 ] that found that a substantial proportion of shelter residents at the IMCC site obtained housing within 6 months after referral to the program. Few studies have examined the effects of collaborative mental health interventions on housing outcomes outside of the case management and assertive community treatment literature.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…With regards to housing, significant reductions in the mean number of days spent in shelters and streets were observed in both groups over the follow-up period. This finding is consistent with an earlier study by Stergiopoulos et al[ 40 ] that found that a substantial proportion of shelter residents at the IMCC site obtained housing within 6 months after referral to the program. Few studies have examined the effects of collaborative mental health interventions on housing outcomes outside of the case management and assertive community treatment literature.…”
Section: Discussionsupporting
confidence: 93%
“…Housing First and case management programs such as ICM and ACT have been shown to improve housing stability, mental health, and substance use outcomes in this population [ 20 , 21 , 23 ], however, the availability of these programs is limited in many jurisdictions [ 15 , 80 , 81 ]. Shelter-based collaborative care models avoid long waiting lists for primary and specialty services [ 40 ], and allow for timely access to coordinated, less intensive supports. These models may have an important role in the continuum of services available to people experiencing homelessness and mental illness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One step to reduce that risk is to increase access to immediate, safe, affordable, permanent housing. Indeed, when combined with quality mental health services, secure, supportive housing has been shown to lead to significant improvements in mental health outcomes among formerly homeless citizens (Stergiopoulos et al 2008). Thus, we believe that emphasis must also be placed—within both research and public policy—on developing housing-based mental health programs for homeless women.…”
Section: Discussionmentioning
confidence: 99%
“…Medication non-adherence is an important problem among people with psychiatric disorders experiencing homelessness. Adherence to prescribed psychotropic drugs is associated not only with improved clinical outcomes but also improved housing outcomes ( 1 ). However, a minority (as low as 12%) of homeless individuals reach therapeutic efficacy with their prescribed psychotropics ( 2 ).…”
Section: Introductionmentioning
confidence: 99%